Mobile Learning-Based Pocketbook Development in Educational Field Practice in Increasing the Competency of Professional Teachers - Sri Mariya; Azwar Ananda; Syafri Anwar; Erianjoni Erianjoni; Maria Montesori (International Journal of Educational Dynamics, 2022)
Teacher professionalism reflects the attitude, knowledge, and skill they have. Professional teachers are teachers with the necessary qualifications in carrying out the teaching and learning process which includes knowledge, social, attitude, and professional skills competencies. Teacher professional competence accompanies Law Number 20 of 2003 which has been defined regarding an education system that demands superior teachers, a spirit of professionalism, ethics, and commitment in carrying out their duties. A pocketbook based on mobile learning in education with the matter of increasing the competence of professional teachers is a form of implementation of developments in the world of education in the 21st century. The importance of developing a pocketbook with one of these models is to accompany the above learning through critical thinking, collaboration, creativity, innovative, and communication. The development of this book aims to prepare professional teacher candidates when conducting Educational Field Practices (EFP) in schools. Through the pocketbook, prospective professional teachers are expected to be able to plan learning programs, carry out learning, assess the learning process, master teaching materials, and implement them in the teaching and learning process.